Peran Jaksa Pengacara Negara dalam Pengembalian Kerugian Keuangan Negara - Gladly Rifqi Samhudi; Sodikin Sodikin (AHKAM, 2026)
The State Attorney (JPN) is part of the Prosecutor’s Office of the Republic of Indonesia, which has the authority to represent the state or government in civil and state administrative cases, both inside and outside the court. One of the strategic roles of the JPN is to pursue the recovery of state financial losses resulting from default, unlawful acts, or administrative disputes involving state institutions. This study aims to analyze the forms of the State Attorney’s role in litigation and non-litigation processes and to describe the legal procedures undertaken in recovering state financial losses. This study used a descriptive qualitative method with a document study and legal literature approach. Data were obtained from laws and regulations, court decisions, academic journals, and prosecutorial policy documents. The results showed that the role of the JPN includes preventive actions through the provision of legal opinions and legal assistance, as well as repressive actions through civil lawsuits, the implementation of court decisions, and asset execution. The legal procedures undertaken were carried out systematically, beginning with the request for power of attorney, case review, non-litigation settlement, litigation, and execution. The conclusion of this study affirms that the State Attorney has an important role in supporting the recovery of state financial losses through civil and state administrative law instruments. These findings imply the need to strengthen the JPN’s function in providing legal assistance, resolving disputes effectively, and optimizing the recovery of state losses in an accountable manner.